Gamma ray detection with CHIMERA at LNS: results and perspectives. (June 2020) - Cardella, G; Favela, F; Martorana, N S; Acosta, L; Andres, M V; Camaiani, A; De Filippo, E; De Luca, S; Gelli, N; Geraci, E; Gnoffo, B; Guazzoni, C; et al.
Abstract: We describe the use of the 4tt CHIMERA charged particle detector as a large efficiency y-ray detector. The CsI(Tl) stage of the CHIMERA telescope is used to detect and identify y-rays. The high detection efficiency and the sufficient energy resolution guaranteed by CsI(Tl) allows us to use the detector for the study of rare decays. Two examples are reported: the low probability gamma decay (<10%) of the Pygmy resonance of a radioactive nucleus as the 68 Ni; the measurement of the gamma decay probability of excited levels of 12 C as the Hoyle state at 7.65 (∼10 −4 ) MeV and the 3- level at 9.64 MeV (∼10 7 ), both important for the Carbon production in stars. Future experiments made possible at INFN-LNS by the availability of the new fragment separator FRAISE are also outlined.